Pengetahuan Berhubungan dengan Konsumsi Tablet Fe Saat Menstruasi pada Remaja Putri di SMAN 2 Banguntapan Bantul - Prasetya Lestari; Widardo Widardo; Sri Mulyani (Alma Ata University Press, 2015)
Preventing of nutritional anemia among adolescents is low, as evidenced by student a senior high school of 2 Banguntapan which Fe tablet consumption during menstruation is still low. So that is necessary knowledge of Fe tablet during menstruation further more. The purpose of this study was to determine the relationship between knowledge and the consumption of Fe tablets during menstruation in adolescent. Analytical survey research design with cross secsional, a number of respondents was 64 with a total sampling technique. Instrument by questionnaire on knowledge and Fe tablet checklist to determine Fe tablet consumption. Techniques of data analysis using fisher excact. The results showed that there are only eight respondents (12.5%) whose consuming Fe tablet during menstruation with enough knowledge category. The results of bivariate analysis by fisher exact p-value=0.321 it’s showed that there was no relationship between knowledge with the consumption of iron tablets during menstruation in adolescent.